2009
DOI: 10.3109/17453670903035559
|View full text |Cite
|
Sign up to set email alerts
|

Similar clinical outcome after unicompartmental knee arthroplasty using a conventional or accelerated care program

Abstract: Background and purpose Over the last 5 years, there has been increasing interest in reducing length of hospitalization (LOS) through accelerated programs. We examined the clinical outcome of patients undergoing a unicompartmental knee replacement (UKR) in an accelerated care program (A group) compared to a conventional care program (C group).Methods 40 patients randomized into 2 groups were included (A group: 17 patients; C group: 23 patients). Nausea, micturition problems, lower limb dysfunction, pain (VAS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…. Thirty‐eight eligible studies with relevant outcomes were found, including two quasi‐randomized studies. In total 67 papers on these studies were reviewed ( Appendix S1 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…. Thirty‐eight eligible studies with relevant outcomes were found, including two quasi‐randomized studies. In total 67 papers on these studies were reviewed ( Appendix S1 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies reporting length of stay had standardized discharge criteria. In one the criteria differed between intervention and control groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…And in addition treating patients in a joint care programme [42,43] • Surgical pre-assessment, planning the admission, post-operative care and planning a safe discharge [44], early imaging with CT, MRI, or nuclear scintigraphy, particularly on the day before or the day of admission [45] • Preventing admissions of patients not needing inpatient care [46][47][48] • Utilising specialised nurse practitioners or other advanced professionals [49][50][51] • Creating an observation unit that gives more time to decide whether or not to admit the patient [52] • Stimulating that patients initially are seen by the right specialty [53] • Performing same-day major surgery [47] • Optimising guidelines and protocols or introducing clinical pathways for specific patient groups in order to reduce the length of stay and often with improvements of quality of care • Treating patients in a fast-track or accelerated care programme [54][55][56][57][58][59][60][61][62] • Choosing a laparoscopic rather than a classic intervention (open surgery) [63][64][65][66][67][68][69][70] although readmission rates for laparoscopic treatment may be higher [71] • Implementing an acute stroke unit [72] • Being aware that consultations, transfers and fragmentation of care often lead to delays [73,74] • Reducing waiting times for examinations [8,48] • Stimulating early rehabilitation and physical activity [75]…”
Section: Matches Between Interventions Proposed By the Professionals mentioning
confidence: 99%